PROBLEMATIKA PERNIKAHAN DINI DI DESA TEBAS SUNGAI KECAMATAN TEBAS - Deya Juliana; Manja (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
Early marriage is a marriage between a man and a woman who is still below the minimum limit stipulated by Law Number 1 of 1974 concerning Marriage. The purpose of marriage is to get offspring, create a harmonious, prosperous and happy family. Marriage at this very young age will invite many unexpected problems because from a physical, material, and mental perspective it is not yet established. So that often there is a collapse in the family. Harmony in the family is not determined by age, because everything is returned to each individual. But age can usually influence the way a person thinks and acts. Early marriage invites a lot of problems in the household, because from a very young age and from a psychological point of view it is not yet established. Problems and differences in understanding trigger conflict. With this young age, it is very difficult to respond to problems that exist in the household.